An implementation digital of voting rights for persons with mental disabilities elections - Chyntia Mulia Ningsih; Ihsan Surya Wibowo; Muhammad Juang Rambe (Jurnal Scientia, 2024)
In practice there are still people with mental disabilities who are not registered as voters in regional elections. 2017 and 2018 as well as the 2019 election. This happened because people with mental disabilities were still considered not legal subjects. This paper based library research methods, with descriptive research, normative legal research type, and the types of data used are primary legal materials, secondary legal materials, tertiary legal materials and data analysis using qualitative methods. The government's efforts to fulfill the rights of persons with disabilities in elections include election outreach, registration of voters with disabilities, preparation of election logistics, preparation of election organizers. The classification of mental disabilities in elections is divided into two, namely people with mental disabilities who have the right to vote in elections and people with mental disabilities who do not have the right to vote in elections.